2002
DOI: 10.3346/jkms.2002.17.6.749
|View full text |Cite
|
Sign up to set email alerts
|

The Skeletal Site-Differential Changes in Bone Mineral Density Following Bone Marrow Transplantation: 3-Year Prospective Study

Abstract: INTRODUCTIONWith improved survival following transplantation, increasing importance is now being placed upon the long-term effects of therapy including osteoporosis. Several reviews regarding bone complications in transplanted patients have appeared in the literature (1-5). Most of these works refer to renal, hepatic, and cardiac transplants, whereas references to bone marrow transplantation (BMT) remain scarce, especially about the long-term changes in bone mineral metabolism. Bone diseases following BMT show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…It was previously reported that bone disease is one of the complications of a BMT. 1,5 According to Castaneda et al, 9 33 and 18% of BMT recipients had osteopenia and osteoporosis in the lumbar spine when examined 33.6 months after BMT. The main causes of bone loss following a BMT include the use of immunosuppressants and hypogonadism induced by TBI or chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously reported that bone disease is one of the complications of a BMT. 1,5 According to Castaneda et al, 9 33 and 18% of BMT recipients had osteopenia and osteoporosis in the lumbar spine when examined 33.6 months after BMT. The main causes of bone loss following a BMT include the use of immunosuppressants and hypogonadism induced by TBI or chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The post-BMT bone loss is mainly related to the immunosuppressants and the gonadal dysfunctions secondary to myeloablative therapy and/or total body irradiation (TBI). [1][2][3][4][5] The rapid impairment in bone formation and the increase in bone resorption, as mirrored by the biochemical markers, might play a role in bone loss, particularly during the early post-BMT period. 1 The pathogenic role of the cytokines is well known in the development of postmenopausal osteoporosis and other forms of secondary osteoporosis.…”
mentioning
confidence: 99%
“…9 Data on the temporal sequence of bone loss in long-term survivors following hematopoietic stem cell transplantation (HSCT) are sparse. [10][11][12][13] However, these patients are exposed to numerous bone toxic factors: induction and consolidation therapy of the underlying hematological disease; malignancy-related changes in bone structure, especially in acute leukemia 14 ; dose-dependent toxicity of high-dose chemotherapy to bone marrow osteoprogenitors 15 ; conditioning regimen for transplantation, including total body irradiation (TBI) 16 ; graftversus-host disease (GVHD) and its treatment with steroids and cyclosporine A 17 ; immobilization; and hypogonadism following TBI. Cross-sectional studies of bone loss after HSCT revealed conflicting data: 5 of 25 patients, examined at least one year after HSCT (mean, 3; range, 1-10 years) showed osteoporotic bone mineral density (BMD) 18 ; 29 long-term survivors with a median survival of 5 years (minimum, 3 years) showed BMD within normal limits (Z-score Ͼ Ϫ1.5) except 2 male patients with hypogonadism.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional studies of bone loss after HSCT revealed conflicting data: 5 of 25 patients, examined at least one year after HSCT (mean, 3; range, 1-10 years) showed osteoporotic bone mineral density (BMD) 18 ; 29 long-term survivors with a median survival of 5 years (minimum, 3 years) showed BMD within normal limits (Z-score Ͼ Ϫ1.5) except 2 male patients with hypogonadism. 19 Prospective studies of bone loss are sparse; [10][11][12][13][20][21][22] the study with longest observation time presents follow-up of 11 patients observed for 3 years. 13 Data demonstrate rapid bone loss during the first 6 months after transplantation (5.7% at the lumbar spine and 6.9% to 8.7% at the femoral neck sites) with no further decline between months 6 and 12 21 and even recovery of bone mass during further follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…6 It has been described after hematopoietic stem cell transplantation (SCT) as well, with the majority of cases reported in alloSCT recipients. [7][8][9][11][12][13][14][15][16][17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34][35] AlloSCT-associated BMD loss is usually described in the first 6-12 months after the transplantation, but varies widely from 40 days 17 to 4-6 years after the transplantation, 30,31,34 and in some instances can persist for 10-12 years. 26,28 Baseline BMD pre-SCT is usually within the normal limits; [15][16][17]24,[27][28][29][30]33 the few exceptions noting high O/O prevalence pre-SCT are probably due to the underlying diseases or intensive chemotherapy prior to the transplantation.…”
Section: Introductionmentioning
confidence: 99%